Outcome of ureteral distensibility on the success of ureteroscopy: A prospective hospital-based descriptive study - D.A. Hameed; A.S. Safwat; M.M. Osman; M.M. Gadelmoula; A. Kurkar; M.A. Elgammal (African Journal of Urology, 2017)
Introduction: “Difficult ureter” is a known problem that increases the complications during ureteroscopy. Objective: To categorize ureters according to their distensibility, and to determine whether ureteric distensibility is associated with the success of ureteroscopy and its complications. Subjects and methods: Between January 2010 and September 2012, we tested ureteral distensibility in 306 patients who had a unilateral single radiopaque ureteral stone, 6–20 mm in diameter. Ureteral distensibility was classified into two categories according to the maximum size of a ureteral dilator that could be introduced before ureteroscopy: non-distensible ureters, which admitted a dilator up to 10 Fr and distensible ureters, which admitted a dilator >10 Fr. Correlations between distensibility and the success rate and complications of ureteroscopy were determined. Results: Overall, 102 patients (33.3%) had non-distensible ureters and 204 (66.7%) had distensible ureters. Distensibility was correlated with the success of ureteroscopy because initial ureteroscopy failed in 38.2% of non-distensible ureters. Ureteroscopy was successful in all distensible ureters. The incidence of ureteric injury was higher in non-distensible ureters than in distensible ureters. Conclusions: Our results suggest that ureteric distensibility should be tested before ureteroscopy. Primary ureteroscopy is recommended in distensible ureters because of its low complication rates and favorable outcome. Pre-stenting may be necessary before ureteroscopy in non-distensible ureters; secondary ureteroscopy may be safer and more feasible in these settings.